2022
DOI: 10.1371/journal.pntd.0010330
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk of cutaneous larva migrans: A case report and a systematic literature review

Abstract: Cutaneous larva migrans (CLM) is a parasitic zoonosis of warm tropical and subtropical areas, although autochthonous cases have been increasingly reported in Western European countries. Data on the prevalence of CLM as an occupational disease in workers exposed to potentially contaminated soil or in close contact with dogs and cats are scant. Herein, we report an autochthonous case of CLM in a dog breeder from southern Italy (Apulia region), along with a systematic literature review describing the risk of CLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, the fact that all adult (age of 18 years and over) patients are male might be attributed to social and healthcare disparities and inequalities that discourage female from seeking healthcare services. This skewed sex ratio is commonly observed across different infectious diseases in the country [9] , [10] , [11] , [12] . Additionally, the relatively high involvement of male in outdoor activities in places that usually contaminated with cats and dogs feces such as beaches and playgrounds is exposing them to higher risk of infection [6] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the fact that all adult (age of 18 years and over) patients are male might be attributed to social and healthcare disparities and inequalities that discourage female from seeking healthcare services. This skewed sex ratio is commonly observed across different infectious diseases in the country [9] , [10] , [11] , [12] . Additionally, the relatively high involvement of male in outdoor activities in places that usually contaminated with cats and dogs feces such as beaches and playgrounds is exposing them to higher risk of infection [6] .…”
Section: Discussionmentioning
confidence: 96%
“…CLM infection is commonly a self-limiting condition with complete healing occurs at the 5th or 6th week after the onset of the disease due to the death of the larvae [12] . The ideal management is treating the symptoms such as pruritic rashes can be treated by the administration of topical or orally antihistamines, and the administration of albendazole for the larvae [12] , [13] , [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Both U. stenocephala and A. caninum can also infect domestic dogs, and U. stenocephala can infect domestic cats [ 17 , 18 ]. A. caninum is considered a zoonotic species, as third-stage larvae contaminating the environment can be responsible for cutaneous larva migrans in humans [ 28 ]. The results showed that the frequencies of hookworm occurrence in the two wild canid species significantly differ according to habitat type.…”
Section: Discussionmentioning
confidence: 99%
“…These zoonotic hookworms responsible for CLM are predominantly found in tropical and subtropical regions across Southeast Asia, Africa, South America, and the Caribbean, and they have been recently reported in the United States, Canada, and Europe [7,8]. Hr-CLM is the most frequent travel-associated skin disease of tropical origin [3,9], and it is likely to be a common disease in local residents, even if underreported.…”
Section: Introductionmentioning
confidence: 99%